1999
DOI: 10.1086/314644
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli and Vaginal Host Defense: Activation of the Human Immunodeficiency Virus Type 1 Long Terminal Repeat, Cytokine Production, and NF‐κB

Abstract: Lactobacilli, a component of the normal vaginal flora, can activate the human immunodeficiency virus (HIV)-1 long terminal repeat (LTR) in the Jurkat T lymphocyte and THP-1 macrophage cell lines. Activation of the LTR in Jurkat cells was strongly enhanced by vanadate and inhibited by catalase, implicating H2O2. In contrast, activation in THP-1 cells occurred in the absence of vanadate and was unaffected by catalase. The active material partitioned into the phenol layer on hot aqueous phenol extraction. Lactoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…Our results are in contrast with the report by Klebanoff et al [33], which shows that L. acidophilus (strain crispatus) activates HIV-LTR transcription. Variation among L. acidophilus (strain crispatus) and the 2 strains tested by our laboratory could explain the differences in HIV-LTR induction activities.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in contrast with the report by Klebanoff et al [33], which shows that L. acidophilus (strain crispatus) activates HIV-LTR transcription. Variation among L. acidophilus (strain crispatus) and the 2 strains tested by our laboratory could explain the differences in HIV-LTR induction activities.…”
Section: Discussioncontrasting
confidence: 99%
“…In support of this hypothesis, Klebanoff et al (1999) have shown that L. crispatus, which is present in the normal vaginal flora, induces TNFα secretion and activation of NF κB and the HIV LTR.…”
Section: Discussionmentioning
confidence: 78%
“…In vitro, lactobacilli (constituents of the normal vaginal flora) and Gardnerella vaginalis have been shown to enhance HIV-1 expression in mononuclear cells by a mechanism involving nuclear factor kB and the HIV long-terminal repeat promoter [33,34]. This may be the result of TNF-a signal transduction [34].…”
Section: Discussionmentioning
confidence: 99%